The Prevalence of "at Risk" Eating Disorders among Athletes in Jordan - Hadeel A. Ghazzawi; Omar A. Alhaj; Lana S. Nemer; Adam T. Amawi; Khaled Trabelsi; Haitham A. Jahrami (MDPI AG, 2022)
Eating disorders (EDs) are addressed as one of the expanding mental health problems worldwide. While an ED is a clinical psychiatric diagnosis that can only be established after a psychiatric assessment, it is important to note that "at-risk" refers to people who will exhibit aberrant eating patterns but do not fully meet the requirements for an ED diagnosis. This study was designed to address the ED symptoms (i.e., "at-risk") in Jordanian athletes and their association with age, sex, body mass index (BMI), and type of sport. A convenient, cross-sectional study was conducted among 249 athlete participants by answering the Eating Attitude Test (EAT-26). The EAT-26 results indicated an ED prevalence of 34% among Jordanian athletes. Within "at-risk" ED athletes, sex, age, and BMI had no significant differences in the rates of EDs. Outdoor sports had the least effect on EDs, while the highest was amongst gymnastics. EDs prevalence is alarming among Jordanian athletes. Gymnastics is a risk factor for increasing EDs. Our results should be taken into consideration by physicians, mental health professionals, sports nutritionists, coaches, and sport medicine specialists. We recommend establishing strategies pertaining to mental health, especially EDs in sports centers, along with screening programs for those who demand additional assessment and supervision.